Energy Dissipation on the Ogee Spillways by Using Direction Diverting Blocks (Journal of Engineering, 2016)
The purpose of this study is to evaluate the hydraulic performance and efficiency of using direction diverting blocks, DDBs, fixed on the surface on an Ogee spillway in reducing the acceleration and dissipating the energy of the incoming supercritical flow. Fifteen types of DDB models were made from wood with a triangulate shape and different sizes were used. Investigation tests on pressure distribution at the DDBs boundaries were curried out to insure there is no negative pressures is developed that cause cavitation. In these tests, thirty six test runs were accomplished by using six types of blocks with the same size but differ in apex angle. Results of these test showed no negative pressures developed at the boundaries of these blocks. A physical model for a part of Mandili Dam spillway system was constructed with a scale ratio of 1:50. Thirteen runs were carried out to obtain the rating curve of the ogee weir of Mandili Dam Model. Four hundred and seventy test runs were carried out to investigate the performance of the DDBs in reducing the energy of the flow. In these test runs, nine types of blocks with different sizes and different apex angles installed with different configurations on the spillway surface. Thirteen configurations of DDBs were tested. The Froude Number and the location of the hydraulic jump were used as indicators for the efficiency of these DDBs. Results indicated that when using the DDBs on a spillway surface, less Froude Number downstream the spillway is obtained and the hydraulic jump occurs at a much shorter distance from the spillway toe compared to same spillway without DDBs. Depending on the DDBs type, configuration, and the applied discharge, the obtained reduction in Froude Number varied between 4.4 to 19.3% and the reduction in the hydraulic jump distance measured from the spillway toe varied between 54% and 76% compared with that of the standard design of Mandili Dam.